PREMENSTRUAL SYNDROME (PMS) IN ADOLESCENTS AT SMPN 2 SIDOARJO - Rachmanda, Salsabilla; Suprianto (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Abstract Introduction: Premenstrual syndrome (PMS) is a cyclical disorder that commonly occurs in young and middle women that occurs during the luteal phase of the menstrual cycle, usually occurring regularly 7-14 days before the arrival of menstruation. In women aged 18-49 years in the United Kingdom, PMS symptoms have an impact on quality of life. Premenstrual Syndrome (PMS) is the most common health problem reported by women of reproductive age. Women of childbearing age (women of reproductive age) are women aged 18-49 years who are single, married or widowed. There are facts which reveal that some adolescents experience the same symptoms and the same strength of Premenstrual Syndrome (PMS) as experienced by older women. Purpose: This study was used to determine premenstrual syndrome (PMS) in adolescents at SMPN 2 Sidoarjo. Method: The research design given is descriptive using quantitative methods, the sampling technique is total sampling and the number of 50 respondents is obtained. Data collection was carried out by distributing questionnaires. Results: Of the 50 female respondents at SMPN 2 Sidooarjo, 50% had moderate PMS, 42% had mild PMS, and 8% had severe PMS. It can be concluded that female students at SMPN 2 Sidoarjo tend to experience moderate PMS. Analysis: the analysis in this scientific paper uses cross tabulation. Discussion: And the results of this study concluded that PMS can occur in every teenager and can be influenced by age and weight.